2003
DOI: 10.1029/2002jd003266
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence of the long‐range transport and vertical distribution of free tropospheric aerosols over east Asia: On the basis of aircraft and lidar measurements and isentropic trajectory analysis

Abstract: [1] Seasonal changes in the vertical structure of free tropospheric aerosols over east Asia, on the basis of aircraft-borne and lidar measurements, and on the pathway of the longrange transport of Asian dust particles inferred from isentropic trajectory analysis are discussed. Aircraft-borne measurements held in situ in the free troposphere over central Japan in 2000-2001 revealed a small in scale yet steady transport of dust in the lowermiddle free troposphere (2-6 km altitude) during spring including days wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 32 publications
(38 reference statements)
2
44
0
2
Order By: Relevance
“…The morphology and chemical constituents of individual particles were analyzed using a Scanning Electron Microscopy (SEM) with an energy dispersive X-ray spectrometer (EDS). The criteria used for the particles identification are described by Matsuki et al (2008): presence of a dust particle can be identified by the typical irregular shape and the dominant X-ray peaks corresponding to Al and Si; particles rich in Cl and K are linked to biomass burning; and particles found enriched by P and K may be attributed to biogenic origin. The ATR-42 was also equipped for the measurements of wind, turbulent fluxes, and atmospheric state parameters.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology and chemical constituents of individual particles were analyzed using a Scanning Electron Microscopy (SEM) with an energy dispersive X-ray spectrometer (EDS). The criteria used for the particles identification are described by Matsuki et al (2008): presence of a dust particle can be identified by the typical irregular shape and the dominant X-ray peaks corresponding to Al and Si; particles rich in Cl and K are linked to biomass burning; and particles found enriched by P and K may be attributed to biogenic origin. The ATR-42 was also equipped for the measurements of wind, turbulent fluxes, and atmospheric state parameters.…”
Section: Instrumentationmentioning
confidence: 99%
“…A two-stage low-volume impactor with 50% aerodynamic cutoff diameters of 0.2 and 1.6 µm was used to collect particles on electron microscope grids (Matsuki et al, 2003).…”
Section: Instrumentationmentioning
confidence: 99%
“…Furthermore, SYNOP (surface synoptic observations) database indicated that dust events occurred at several sites in the continental desert areas for 3 days before the sampling dates. During the spring and summer seasons, the prevailing westerly winds is thought to constantly carry dust particles throughout the free troposphere and cause the weak Kosa at a height of 4000 m over East Asia (Iwasaka et al 1988;Matsuki et al 2003). Kosa events have been reported to increase the number of airborne microorganisms on ground surfaces in correspondence with the amount of mineral particles (Hara and Zhang 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, aerosol data above the altitude of 5 km were not included because aerosols of high altitudes were not measured during aircraft observations. In the spring season, aerosols above the altitude of 5 km may play an important role on AOT because dust aerosol, which has a large extinction cross-sectional area, may exist at high altitudes (e.g., Hayasaka et al 1990;Matsuki et al 2003). Further, aerosols larger than 3.12 mm in diameter, which were not measured during aircraft observations, were also important to increase AOT because of their large extinction crosssectional areas.…”
Section: Aerosol Optical Thickness (Aot)mentioning
confidence: 99%
“…Coarse mode (d > 1:0 mm) aerosols were considered to be dust because Asian dust events frequently occur in the spring season as the developing cyclone passes through desert areas every several days . Some researchers (e.g., Iwasaka et al 1988;Matsuki et al 2003) detected dust aerosol in the free troposphere even during no dust events. Hayasaka et al (1990) also found dust aerosol at high altitudes above marine air masses.…”
Section: Aerosol Optical Thickness (Aot)mentioning
confidence: 99%